QUANTITY OF FISH MEAL PROCESSED FROM SUN-DRIED FISH IN A COMMERCIAL FISH MEAL DRYER - RAO, D RAMANANDA; KAMASASTRI, P V (Fishery Technology, 2025)
The physical and chemical compositions of the raw materials received and the composition and nutritive values of the finished products in a commercial size fish meal plant employing the dry rendering process were studied and reported in this paper.